Initial results of early gastrointestinal cancer treatment using endoscopic submucosal dissection at 19-8 hospital - Thanh Tuyen, Hoang; Viet Dung, Nguyen; Viet Anh, Pham Thi; Phuong Thao, Doan Thi; Duc Pham, Van; Van Khanh, Ho Thi; Hong Khanh, Haz Thi; Thu Hang, Nguyen Thi; Ánh Durong, Nguyen; Tran Duc, Canh (Investigaciones Medicoquirúrgicas, 2024)
Introduction: Early-stage cancer is defined as cancer confined to the mucosal or submucosal layers (T1 stage) without lymph node metastasis. Objective: To evaluate the outcomes of endoscopic submucosal dissection in treating early-stage gastrointestinal cancer. Methods: A prospective descriptive study involving 20 patients with early-stage gastrointestinal cancer treated using endoscopic submucosal dissection at the Gastroenterology Department of 19-8 Hospital from September 2023 to September 2024. Results: Average procedure duration: 62-180 minutes; lesion size: 6-45mm; in bloc resection rate: 100 %; bleeding complication rate: 5 %; average hospital stay: 3-8 days; lesion locations: hypopharynx, esophagus, stomach, colon, and rectum. Conclusions: Endoscopic submucosal dissection is an effective and relatively safe technique for treating early-stage cancer. Complications such as perforation and bleeding can occur but are manageable. Endoscopic submucosal dissection allows for en bloc lesion removal, enabling pathologists to accurately assess resection margins through histopathological results. During endoscopy, careful observation is necessary to avoid missing lesions, especially when the scope passes through the stimulated hypopharynx.